The Wisdom of Mentor. (May 2022) - Norman, Jesse
Abstract: Thomas Hobbes posited a social contract which legitimates sovereign authority. But what grounds, or could ground, such a contract? Through reflection on Oakeshott, and on Aristotle's Nichomachean Ethics, the paper argues for a so far unrecognised mode of human association: philic association. It briefly considers a possible expression of philic association in the history of English law, before making the case for programmes of mentoring as a policy both reflective and supportive of this mode. It ends by suggesting that the existence of such a mode shows why Hobbes's social contract theory, however ingenious and influential it has proven to be, is neither sufficient nor necessary for its stated purpose.